Respuesta :
The first thing you should do for this case is to select x from the given equation to find the original number. Then clearing x we have
2x + 24 = 2 / 7x.
2x - 2 / 7x = -24
x (2-2 / 7) = - 24
x ((14-2) / (7)) = - 24
x ((12) / (7)) = - 24
x = -24 * ((7) / (12)) = - 14
answer
the original number 14
2x + 24 = 2 / 7x.
2x - 2 / 7x = -24
x (2-2 / 7) = - 24
x ((14-2) / (7)) = - 24
x ((12) / (7)) = - 24
x = -24 * ((7) / (12)) = - 14
answer
the original number 14
Let x be the number.
Twice the number is 2x.
Adding 24,we have 2x + 24 -----(1)
But expression (1) is the same as 2/7 of original number. I. e 2/7x
So 2x + 24 = (2/7)x
So 2x - (2/7)x = -24
x(2 - (2/7)) = -24
x = -24 / (2 -(2/7))
x = - 24 / 1.714
x = - 14.0023
x = -14